2006
DOI: 10.2337/dc08-0500
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Point-of-Care Nerve Conduction Device for the Detection of Diabetic Sensorimotor Polyneuropathy

Abstract: OBJECTIVE -The diagnosis of diabetic sensorimotor polyneuropathy using objective electrophysiological tests is hindered by limited access to the specialized laboratories and technicians that perform and interpret them. We evaluated the performance characteristics of a novel portable and automated point-of-care nerve conduction study device, which can be operated by nontechnical personnel, and compared it with conventional nerve conduction studies performed in a specialist setting.RESEARCH DESIGN AND METHODS -S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
71
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 25 publications
2
71
0
2
Order By: Relevance
“…In patients with type 1 and type 2 DM, this original device again resulted in reasonable agreement with conventional NCS parameters (the reference standard) performed by electromyography technicians, and it could accurately identify DPN in both type 1 and type 2 DM patients [12,13]. Spearman coefficients for correlation between the SNAP of the point-of-care and conventional NCS was high: 0.95 (with p < 0.001) [12].…”
Section: The First Nc-stat® Devicementioning
confidence: 75%
See 4 more Smart Citations
“…In patients with type 1 and type 2 DM, this original device again resulted in reasonable agreement with conventional NCS parameters (the reference standard) performed by electromyography technicians, and it could accurately identify DPN in both type 1 and type 2 DM patients [12,13]. Spearman coefficients for correlation between the SNAP of the point-of-care and conventional NCS was high: 0.95 (with p < 0.001) [12].…”
Section: The First Nc-stat® Devicementioning
confidence: 75%
“…Spearman coefficients for correlation between the SNAP of the point-of-care and conventional NCS was high: 0.95 (with p < 0.001) [12]. However, Bland and Altman statistical method showed a slight underestimation of SNAP by an average of 1.2 ± 3.4 μV with the point-of-care device in comparison with the reference method [12]. In spite of this systematic bias (which is reported as clinically unimportant by the authors), quantitative agreement as demonstrated by the Bland and Altman method was strong [12].…”
Section: The First Nc-stat® Devicementioning
confidence: 98%
See 3 more Smart Citations